G256 Validation of transcutaneous bilirubinometry as a method to monitor newborn jaundice in a low income country. (12th March 2018) - Johnson, S; Marseille, C; Toussaint, P; Hill, C; Vasu, V; Battersby, C
Abstract : Background and aims: Kernicterus is a significant problem in low income countries (LICs) and measurement of total serum bilirubin (TSB) is often restricted by cost or lack of laboratory facilities. Near patient testing through the use of transcutaneous bilirubinometry (TcB) may be of benefit in LICs. Therefore, the aim of this study was to determine agreement between (TcB) and TSB in a LIC (Haiti). Methods: With approval the Ministry of Health, we conducted a single centre prospective study (February-May 2017) in a NGO funded neonatal unit in northern Haiti. Babies with clinically detected jaundice, <7 days of age were eligible for inclusion. To enable serial TcB measurements during phototherapy, a strip of black tape was placed across the babies' sternum. Once clinical jaundice was detected, a parallel TcB measurement using a TcB bilirubinometer (JM-103) and a blood TSB sample for laboratory testing were obtained. Further management was initiated based upon the UK NICE threshold bilirubin values. A Bland-Altman difference plot was used to measure agreement between TcB and TSB. Results: Paired TcB/TSB measurements were obtained from 35 infants. 19 (54.3%) were male; 23 (65.7%) were ≥35 weeks, 12 (34.3%)<35 weeks gestation. All babies were ≤5 days old and 32 (91.4%) were receiving phototherapy. A Bland-Altman plot of TcB versus TSB demonstrated good agreement between the methods with only one TcB/TSB pair falling outside of the mean difference 95% confidence (CI) interval (Bland-Altman plot available). Overall, TcB tended to overestimate bilirubin in comparison to TSB [mean difference 11.1 µmol/L (95% CI −10.2, 32.5)]. However, at higher bilirubin levels (>200 µmol/L), TcB tended to underestimate bilirubin in comparison to TSB and the magnitude of the difference increased. The mean difference between TcB and TSB was increased in babies<35 weeks [16.4 µmol/L (95% CI: 24.8 to 57.5)] compared to babies>35 weeks 8.4µmol/L (95% CI −18.5, 35.3). Conclusion: Our data indicate good agreement between TcB and TSB levels in Haitian newborns receiving phototherapy. Implementing TcB measurement for the management of newborn jaundice is both feasible and convenient as an alternative to laboratory TSB measurements in preterm and term babies during phototherapy in a LIC setting.